The performance of beta type stirling engine using different fuel - Ng, X. H.; Bakar, R.A.; Kadirgama, Kumaran; Subramonian, Sivarao; Ramasamy, Devarajan; Samykano, Mahendran (2023)
Stirling engine categorized as external combustion engine which defined as a closed-cycle regenerative heat engine to perform the conversion of energy into the mechanical power. The thermal efficiency of the Stirling cycle always is the main criterion, and the literature showed its efficiency of energy conversion is consider relatively as high as the Carnot cycle. Although the Stirling engine consists of great versatility for energy sources, however still inadequate efforts were done for the